Recovery journey of people with a lived experience of schizophrenia: a qualitative study of experiences - Min Ma; Zhidao Shi; Yanhong Chen; Xiquan Ma (BMC Psychiatry, 2023)
Abstract Background Mental health recovery involves an integration of clinical and psychosocial frameworks. The recovery journey of individuals diagnosed with schizophrenia and the factors that influence it have been extensively studied. Because the recovery journey is culturally influenced, we examined the recovery process expriences of individuals diagnosed with schizophrenia in China, focusing on the influence of a Confucian-dominated collectivist and family-centred culture. Methods An Interpretive Phenomenological Analysis (IPA) study was conducted; data were gathered through in-depth interviews with 11 individuals with lived experience of schizophrenia. Results Four themes were identified in this study: traumatic illness experiences, influence of the family, motives for recovery, and posttraumatic growth, comprising ten subthemes. “For the family” and “relying on oneself” are the main drivers of recovery for individuals with a Chinese cultural background. Some people believe that taking care of themselves is an important way to ease the burden on their families and treat them well. There is a link between ‘for the family’ and ‘relying on oneself. Conclusions Individuals living with schizophrenia in China have undergone significant traumatic experiences and have profound interactions with their families. Post-traumatic growth reflects an increase in the individual’s connection to others and individual agency. It also suggests that the individual is not receiving enough support outside of the family. The impact of individual agency and family relationships should be considered in services that promote recovery, and clinic staff should enhance support outside the home to the individuals.